Motivations, risks, and constraints: An analysis of affective and cognitive images for cannabis tourism in Canada - Lena Jingen Liang; Hwansuk Chris Choi; Susan Dupej; Alireza Zolfaghari (Annals of Tourism Research Empirical Insights, 2023)
The aim of this study was to explore Canada's image as a cannabis tourism destination and investigate how tourists' motivations, perceived risks, and travel constraints affect their intentions to visit Canada for leisure cannabis consumption. By examining the image formation process from a pre-travel perspective, this study investigated the impacts of motivation, perceived risks, and travel constraints on the affective and cognitive images that contribute to the formation of a pre-travel image and visiting intention for cannabis tourism. Empirical results indicated that potential cannabis tourists' visiting intentions were influenced more by their affective image towards Canada than their cognitive image. Furthermore, perceived risk fully mediated the relationship between cognitive image and visiting intention. These findings provide valuable insights for local governments, destination marketing groups, and businesses interested in developing the cannabis tourism market.
Keywords: 330; Destination image; Travel intention; Marijuana legalization; Canada; Cannabis tourism